2021
DOI: 10.1371/journal.pone.0256721
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted forward and backcross breeding for improvement of elite Indian rice variety Naveen for multiple biotic and abiotic stress tolerance

Abstract: The elite Indian rice variety, Naveen is highly susceptible to major biotic and abiotic stresses such as blast, bacterial blight (BB), gall midge (GM) and drought which limit its productivity in rainfed areas. In the present study, a combined approach of marker-assisted forward (MAFB) and back cross (MABC) breeding was followed to introgress three major genes, viz., Pi9 for blast, Xa21 for bacterial blight (BB), and Gm8 for gall midge (GM) and three major QTLs, viz., qDTY1.1, qDTY2.2 and qDTY4.1 conferring inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In their investigation, proteome profiling for tolerant lines confirmed gene colocalization in the salinity tolerance QTL intervals mapped in the RIL population [ 57 ]. Rahman et al screened RILs derived from IR29/Hasawi and identified eight hotspots conferring salinity tolerance across environments colocalised on chromosomes 1, 4, 6, 8, and 12 [ 83 , 133 ].…”
Section: Rice Breeding With Marker Assistance For Salt Tolerancementioning
confidence: 99%
“…In their investigation, proteome profiling for tolerant lines confirmed gene colocalization in the salinity tolerance QTL intervals mapped in the RIL population [ 57 ]. Rahman et al screened RILs derived from IR29/Hasawi and identified eight hotspots conferring salinity tolerance across environments colocalised on chromosomes 1, 4, 6, 8, and 12 [ 83 , 133 ].…”
Section: Rice Breeding With Marker Assistance For Salt Tolerancementioning
confidence: 99%
“…Consequently, the urgent need to breed rice varieties with enhanced resistance has been recognized ( Khush, 2005 ). Recently, several resistant genes against blast and BLB have been utilized in breeding programs to improve both elite rice varieties and parental lines of hybrids through Marker-Assisted Selection (MAS) ( Dixit et al., 2020 ; Singh et al., 2022 ; Janaki Ramayya et al., 2021 ). However, deploying a single resistance gene often leads to rapid breakdowns.…”
Section: Introductionmentioning
confidence: 99%
“…A key limitation in the ability of breeding programmes to leverage these benefits of major‐gene marker‐assisted selection is the availability of those genes in an appropriate elite germplasm (Janaki Ramayya et al, 2021; Wu et al, 2014). Studies on current breeding programmes have shown that about half of the genes and QTLs that could be useful are not found in current elite material; a further 15% or so are present at very low frequency (Cobb, Juma, et al, 2019; Juma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%